The LonB protease controls membrane lipids composition and is essential for viability in the extremophilic haloarchaeon Haloferax volcanii - Cerletti, Micaela (2014)
Although homologs of the ATP-dependent Lon protease exist in all domains of life, the relevance of this protease in archaeal physiology remains a mystery. In this study, we have constructed and phenotypically characterized deletion and conditional lon mutants in the model haloarchaeon Haloferax volcanii to elucidate the role of the unusual membrane-bound LonB protease in archaea. Hvlon could be deleted from the chromosome only when a copy of the wild type gene was provided in trans suggesting that Lon is essential for survival in this archaeon. Successful complementation of the lethal phenotype of ΔHvlon was attained by expression of the heterologous protease gene Nmlon from the haloalkaliphilic archaeon Natrialba magadii, meaning that the biological function of Lon is conserved in these organisms. Suboptimal cellular levels of Lon protein affected growth rate, cell shape, cell pigmentation, lipid composition and sensitivity to various antibiotics. The contents of bacterioruberins and some polar lipids were increased in the lon mutants suggesting that Lon is linked to maintenance of membrane lipid balance which likely affects cell viability in this archaeon. The phenotypes associated to a membrane-bound LonB protease mutant were examined for the first time providing insight on the relevance of this protease in archaeal physiology.